2016
DOI: 10.3389/fpsyg.2015.01905
|View full text |Cite
|
Sign up to set email alerts
|

What Happens in a Moment

Abstract: There has been evidence for the very brief, temporal quantization of perceptual experience at regular intervals below 100 ms for several decades. We briefly describe how earlier studies led to the concept of “psychological moment” of between 50 and 60 ms duration. According to historical theories, within the psychological moment all events would be processed as co-temporal. More recently, a link with physiological mechanisms has been proposed, according to which the 50–60 ms psychological moment would be defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
3
20
0
6
Order By: Relevance
“…300 ms are subjects able to sequentially distinguish and temporally control each individual finger tap (Peters 1989, Wittmann et al 2001). These and many other studies show how sequentially evolving events are temporally integrated in discrete windows or processing cycles (for overviews, see Elliott and Giersch 2016, Pöppel 1997, van Wassenhove 2009, Wittmann 2011. Overall, temporal integration of stimuli with sub-second duration happens over several different time It is on the time scale of around 300 ms that Dainton (2008) identifies the duration of the extensional present: "Tap a table with your fingers, at regular intervals of about a second;…”
Section: Perception Of Temporal Order and Temporal Integrationmentioning
confidence: 89%
See 2 more Smart Citations
“…300 ms are subjects able to sequentially distinguish and temporally control each individual finger tap (Peters 1989, Wittmann et al 2001). These and many other studies show how sequentially evolving events are temporally integrated in discrete windows or processing cycles (for overviews, see Elliott and Giersch 2016, Pöppel 1997, van Wassenhove 2009, Wittmann 2011. Overall, temporal integration of stimuli with sub-second duration happens over several different time It is on the time scale of around 300 ms that Dainton (2008) identifies the duration of the extensional present: "Tap a table with your fingers, at regular intervals of about a second;…”
Section: Perception Of Temporal Order and Temporal Integrationmentioning
confidence: 89%
“…Related conceptualizations have focused on temporal integration mechanisms that are bound to neural system states defining a 'perceptual moment' (e.g. Elliott and Giersch 2016, Pöppel 1997, Stroud 1955, White 2018.…”
Section: Perception Of Temporal Order and Temporal Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea that conscious percepts fall into discrete temporal frames has a long history: something like it appeared over 2,000 years ago in Buddhist thinking (Herzog, Kammer, & Scharnowski, 2016;Pockett et al, 2011). In more recent scientific work it may date back to von Baer (1862) 2 , although the original presentation does not survive and there is uncertainty about its content (Elliott & Giersch, 2016). Elliott and Giersch (2016) stated that von Baer had proposed "a fundamental quantum of experienced time" (Elliott & Giersch, 2016, p. 1) with a duration of about 55 ms.…”
Section: : Early Proposalsmentioning
confidence: 99%
“…In more recent scientific work it may date back to von Baer (1862) 2 , although the original presentation does not survive and there is uncertainty about its content (Elliott & Giersch, 2016). Elliott and Giersch (2016) stated that von Baer had proposed "a fundamental quantum of experienced time" (Elliott & Giersch, 2016, p. 1) with a duration of about 55 ms. This is consistent with research by Brecher (1932) showing a nonsimultaneity threshold of about 55 ms with both tactile and visual stimuli although, as we shall see, more recent research has shown a wide range of nonsimultaneity thresholds and Brecher's results can no longer be regarded as definitive in that respect.…”
Section: : Early Proposalsmentioning
confidence: 99%